Phylogenetic relationships of Hemidactylus geckos from the Gulf of Guinea islands: patterns of natural colonizations and anthropogenic introductions estimated from mitochondrial and nuclear DNA sequences - Jesus, José (2020)
Mitochondrial DNA (12S rRNA, 16S rRNA, and cytochrome b) sequences and nuclear sequences (C-mos and alpha-Enolase) were analyzed within all known Hemidactylus species from all three volcanic islands in the Gulf of Guinea that have never been connected to the continent. These comprise both endemic and widespread species. Our aim was to determine if the widespread species was introduced anthropogenically, to determine the number of distinct genetic lineages within the islands, and to determine if the endemic forms constituted a monophyletic group. Our results suggest that a previously undescribed species on São Tomé is the sister taxon to Hemidactylus newtoni, endemic to Annobon. Genetic variation between populations of Hemidactylus greefii from São Tomé and Principe is very high based on mtDNA sequences, but the forms cannot be distinguished using the nuclear DNA sequences. Hemidactylus mabouia appears to have been anthropogenically introduced to all three islands. The island endemics do not form a monophyletic group, suggesting multiple independent colonizations of the islands.